2004
DOI: 10.1063/1.1767095
|View full text |Cite
|
Sign up to set email alerts
|

Some specific features of chaotization of the pulsating barotropic flow over elliptic and axisymmetric sea-mounts

Abstract: A comparison of the chaotic advection in the barotropic inviscid unidirectional pulsating flow over a sea-mount of axisymmetric and elliptic form is presented. The process of passive markers' transport from vortical region into the flow-through region is studied. In particular the evolution of the corresponding Poincaré sections with the change of frequency and amplitude of oscillations is presented. An approach to study the mechanism and parameters of chaotic advection in the open systems with finite lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…3, [16][17][18] The paper concludes with a discussion in Sec. II, we formulate a model for the stream function ͑2͒.…”
Section: ͑2͒mentioning
confidence: 93%
See 3 more Smart Citations
“…3, [16][17][18] The paper concludes with a discussion in Sec. II, we formulate a model for the stream function ͑2͒.…”
Section: ͑2͒mentioning
confidence: 93%
“…3, [15][16][17] It has been found that there exists, at least, a range of perturbation frequencies for which the chaotic transport is maximal. ͑1͒ and ͑2͒ is the problem of dependence of chaotic transport and mixing on perturbation parameters.…”
Section: ͑2͒mentioning
confidence: 99%
See 2 more Smart Citations
“…As it has been mentioned above, we are interested only in the singular perturbations of form (4) (without losing any generality, we put the background flow value to be zero, i.e. q * i = 0 (Kozlov, 175 1995;Izrailsky et al, 2004)). Hence, by setting boundary conditions Φ i | r→∞ = 0, and ∂Φ i /∂r| r→∞ = 0 to Laplace and Helmholtz equations (9), we obtain two sets of Green's function superpositions satisfying system (9) for the upper (m = 1) and middle (m = 2) layer monopole propagation 180 cases,…”
mentioning
confidence: 99%